Carbonatação e absorção capilar em concretos de cimento Portland branco com altos teores de adição de escória de alto forno e ativador químico - Barin, Daniel Sacchet (2008)
The carbonation phenomenon, reaction between CO2 from the atmosphere in the presence of humidity with the Portland cement hydration products, induces pH reduction to levels that can cause the elimination of steel s protective layer, enabling the corrosion mechanism of the steel structure to start.. This is one of the main pathologies in the reinforced concrete and its occurrence depends on the existence of oxygen, humidity and potential difference between two different locations of the steel bar. This research analyzed the performance of different concrete mixtures produced with Portland cement with high levels of blast furnace slag, with and without the chemical activator sodium sulfate (Na2SO4), in relation to compressive strength, capillary absorption and carbonation. For comparison purposes, gray Portland cement concrete test samples were also cast. For the white Portland cement concrete, slag contents of 0% and 50%, without and with chemical activator at concentrations of 4% and 70% were chosen. With the gray Portland cement it was produced concrete with 0% and 50% of slag addition, with and without chemical activator. For each mixture was adopted water/binder ratios of 0.30, 0.42 and 0.55. The samples cast with white Portland cement, destined to the compressive strength tests were broken at 3, 7, 28 and 91 days and the capillary absorption tests were done 91 days after molding. The samples destined to accelerated carbonation tests, cast with the two kinds of cements, were submitted to an atmosphere with 2% CO2 concentration, temperature of 23±1ºC and relative humidity of 75±2%. The carbonation depths determination was realized in the ages of 0, 3, 6, 9 and 12 weeks, after entrance in the chamber. From results obtained it was noticed that compressive strength reduced as the slag content and water/binder ration increased. In more advanced ages, however, the difference in compressive strength between mixtures with slag and the reference mixture was smaller than in the first ages. The capillary absorption reduced with the slag content increase, as a consequence of the refinement pores. The carbonation depth, for the white and gray concretes, increased with the slag content and the chemical activator utilization. In a comparison between white and gray Portland cement concretes, for the same slag content and water/binder ratio, the higher carbonation depths were reached with the white concrete, and this difference was higher when the water/binder ratio was increased.